2012
DOI: 10.1213/ane.0b013e318253622e
|View full text |Cite
|
Sign up to set email alerts
|

Are Ultrasound-Guided Ophthalmic Blocks Injurious to the Eye? A Comparative Rabbit Model Study of Two Ultrasound Devices Evaluating Intraorbital Thermal and Structural Changes

Abstract: Background Since Atkinson’s original description of retrobulbar block in 1936, needle-based anesthetic techniques have become integral to ophthalmic anesthesia. These techniques are unfortunately associated with rare, grave complications such as globe perforation. Ultrasound has gained widespread acceptance for peripheral nerve blockade but its translation to ocular anesthesia has been hampered because sonic energy, in the guise of thermal or biomechanical insult, is potentially injurious to vulnerable eye tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 17 publications
0
30
0
4
Order By: Relevance
“…However, atrophy of the optic nerve is a late complication that may also be caused by direct injury to the central retinal artery or injection or bleeding into the nerve sheath . The arguments against ultrasound techniques, such as the time that they take to learn and perform, should be secondary to safety concerns, particularly as we found that ultrasound prolonged blockade by only 15 s. To limit any heat damage and mechanical disruption that ultrasound can cause to the retina, practitioners should abide by the British Medical Ultrasound Society safety limits, which are a thermal index < 1.0 and a mechanical index < 0.23 . Fewer participants were satisfied with the ultrasound‐guided technique, possibly as a result of discomfort caused by pressure exerted on the eye by the probe.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, atrophy of the optic nerve is a late complication that may also be caused by direct injury to the central retinal artery or injection or bleeding into the nerve sheath . The arguments against ultrasound techniques, such as the time that they take to learn and perform, should be secondary to safety concerns, particularly as we found that ultrasound prolonged blockade by only 15 s. To limit any heat damage and mechanical disruption that ultrasound can cause to the retina, practitioners should abide by the British Medical Ultrasound Society safety limits, which are a thermal index < 1.0 and a mechanical index < 0.23 . Fewer participants were satisfied with the ultrasound‐guided technique, possibly as a result of discomfort caused by pressure exerted on the eye by the probe.…”
Section: Discussionmentioning
confidence: 98%
“…We placed a 22‐G intravenous catheter and sedated participants with intravenous midazolam 2–3 mg and fentanyl 30–50 μg. We placed a B‐Scan linear array ultrasound transducer at the supraorbital rim (Sonomed Escalon; Master‐Vu USB Ultrasound System, New York City, NY, USA), which emitted waves at 12 MHz with a circular footprint focussed at 6 cm . Longitudinal and axial approaches obtained transocular images of the globe and axial length, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Another limitation of the present study is that, although the rabbit eye model has been extensively used in experimental studies, it is also known to present distinct anatomical and physiological differences compared with the human eye (20). Finally, the ocular tissues are particularly susceptible to mechanical and thermal injury associated with excessive ultrasound energy, so that the Food and Drug Administration (FDA) and World Federation for Ultrasound in Medicine and Biology have imposed strict thermal index (TI) and mechanical index (MI) limits for diagnostic ocular ultrasound applications (TI < 1.0, MI < 0.23) (21). The fact that the system employed in this study was not ocular-rated implies that the methodology described may not be directly applicable in human eyes in its present form.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, ultrasound-guided ophthalmic blocks may be impractical because orbitalrated equipment is not readily available in most operating room suites, 6 and technical hurdles may translate into delayed turnover times. We laud the authors for pioneering this technique and stimulating interest for further research.…”
Section: Ultrasound-guided Eye Blocksmentioning
confidence: 99%